Acute graft‐versus‐host disease and bronchiolitis obliterans after autologous stem cell transplantation in a patient with multiple myeloma. Issue 6 (9th April 2015) - Alonso, Sara; Cabrero, Mónica; Caballero, Juan C.; Dávila, Julio; de la Calle, Veronica Gonzalez; López‐Godino, Oriana; López‐Corral, Lucia; Pérez, Estefanía; Vázquez, Lourdes; Corral, Rocío; Caballero, Dolores; del Cañizo, Consuelo; et al.
Key Clinical Message Sixty‐seven‐year‐old patient, diagnosed with multiple myeloma who had received autologous stem cell transplantation, following bortezomib, dexamethasone and thalidomide conventional regimen, achieving complete response, developed rash, diarrhea, and severe respiratory failure, 80 days after the transplantation procedure. He was diagnosed with graft‐versus‐host disease and bronchiolitis obliterans syndrome.